PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET - RATIH KARUNIAWATI (Jurnal Akademika, 2017)
This study aimed to examine the effect of non-performing loans (NPLs) and Loan to Deposit Ratio (LDR) to Return on Assets (ROA). The background of this study was the phenomenon of bank lending is not optimal. The population in this study are all commercial banks listed on the Indonesia Stock Exchange 2011-2015 period. To determine the effect of NPL and LDR to ROA, then used a multiple regression analysis. The research proves that Non Performing Loan (NPL) have a significant and negative effect on the financial performance of state-owned banks in Indonesia with ROA. Loan Debt Ratio (LDR) has a significant influence and positive impact on the financial performance of state-owned banks in Indonesia with ROA. Variables that most dominant influence on ROA is variable NPL. Keywords: non-performing loans, Loan to Deposit Ratio, Return on Assets